الاختيار والتعيين في الحضارة الإسلامية: Selection and Appointment in Islamic Civilization - Masaud, Riham SS; Lubis, Asmuliadi; Noordin, Kamaruzaman (Journal Al-Muqaddimah, 2023)
The selection and appointment are among the important jobs within any institution. The recruitment process has evolved over the ages in terms of principles that are based on selection and appointment. From this standpoint, the selection and appointment process and its impact on the recruitment process in Islamic civilizations will be clarified. This study aimed to introduce selection and appointment as well as the most important Islamic civilizations that were interested in this aspect as it aims to identify the most important successors who were interested in the selection and appointment process. The result reached that civilizations Islamism has provided us with an advanced understanding of the selection and appointment criteria that are based on merit and competence.